2018
DOI: 10.1016/j.jup.2018.08.006
|View full text |Cite|
|
Sign up to set email alerts
|

Sustainable transition in small island developing states: Assessing the current situation

Abstract: Transitioning to sustainable energy systems is an overriding challenge for small islands. Indeed, these territories must succeed within the next decades with the objective of energy independence and transitioning to a sustainable situation. In this research, a statistical approach is performed to explore and discuss a comprehensive study on small islands' sustainability from the standpoint of renewable energy. It is about identifying whether small islands are moving toward a sustainability path. Three steps ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…When considering environmental challenges for SIDS and small hotels, Kelman (2019) examined energy requirements and use (including transportation and waste management) as indicators of environmental sustainability. Climate change impacts on island sustainability and tourism have meant that islands are now at the forefront of energy-related efforts (Praene et al , 2018; Weir, 2018). Given the contribution to climate change made by electricity generation, especially as many islands rely on diesel generators (which is the case in Cyprus) alternative forms of energy generation are needed.…”
Section: Small Island Destinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering environmental challenges for SIDS and small hotels, Kelman (2019) examined energy requirements and use (including transportation and waste management) as indicators of environmental sustainability. Climate change impacts on island sustainability and tourism have meant that islands are now at the forefront of energy-related efforts (Praene et al , 2018; Weir, 2018). Given the contribution to climate change made by electricity generation, especially as many islands rely on diesel generators (which is the case in Cyprus) alternative forms of energy generation are needed.…”
Section: Small Island Destinationsmentioning
confidence: 99%
“…Some of the small hotels use energy saving equipment, such as solar panels and A+ energy saving white goods fitted with smart technology such as electricity generation cards. As outlined by several authors (Praene et al , 2018; Weir, 2018) climate change impacts on island sustainability and tourism have placed islands at the forefront of energy-related efforts. Although the results in general indicated that hoteliers were aware of this, their main efforts for sustainability were for cost saving reasons.…”
Section: Small Hotels In Cyprus and Barriers To Sustainable Tourismmentioning
confidence: 99%
“…Climate change within island sustainability and tourism has placed islands at the forefront of energy-related efforts (Praene, Payet, & Bénard-Sora, 2018;Weir, 2018), given electricity generation's contribution to climate change, especially with many islands relying on diesel generators. Yet many islands experience energy overuse due to tourism (Dodds, 2007b;Ioannides & Holcomb, 2003).…”
Section: Energymentioning
confidence: 99%
“…Two decades ago, islands started the transition from only diesel power plants to hybrid renewable mini-grids to meet ambitious RE targets [7]. Regarding the current prices of RE technologies, hybrid systems are the most cost-effective solution for these territories [8].…”
Section: Introductionmentioning
confidence: 99%